MODEL PEMBELAJARAN PROJECT BASED LEARNING UNTUK MENINGKATKAN KREATIVITAS SISWA SEKOLAG DASAR PADA MATA PELAJARAN SENI BUDAYA DAN KETERAMPILAN (SBDP) - Larasati Wijanarko Putri; Dhina Cahya Rohim; Deki Wibowo (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to determine the effect of the Project Based Learning model on Arts, Culture, and Crafts (SBdP) subjects to Improve Elementary School Students' Creativity. The background of this study is based on the results of initial observations that there are problems with difficulties in developing student creativity in SBdP lessons. This study uses a quasi-experimental method with a one-group pretest- posttest design combined with a description of the process of implementing the model (quantitative descriptive) implemented at SDN 02 Dermolo. The results showed an average pretest score of 59.27 increased to 85.21 in the posttest. The paired sample t-test showed a significant difference between the pretest and posttest results, which means the application of the PjBL model has an effect on increasing student creativity. The N-gain analysis showed an average score of 0.55 or 55% (moderate category). Thus, the PjBL learning model has an effect on student creativity in SBdP subjects. This is evidenced by an increase in creativity scores from the pretest to the posttest which is statistically significant based on the paired sample t-test. The N-Gain value is in the moderate category, indicating that the implementation of PjBL is able to encourage an increase in students' creative thinking skills, including aspects of fluency, flexibility, originality, and elaboration. With observation sheets and assessment rubrics as supporting instruments, the observation scores for each creativity indicator show a good category. This indicates that the PjBL model is able to encourage students to think creatively, produce original ideas, and communicate their work with confidence.